IMMIGRATION EXAMINATION APECT REVIEWED FROM IMO FAL CONVENTION - Gunawan Ari Nursanto (Jurnal Ilmiah Kajian Keimigrasian, 2019)
Indonesia is an archipelago (Archipelago Country) that has territorial borders with other countries covering land, sea or air. As an archipelagic country, Indonesia has regulations regarding the entry and exit of a person, both Indonesian citizens and foreigners. The gate through which someone enters or exits the territory of Indonesia or what is called the Immigration Checkpoint is a crossing place for everyone. With the existence of the Immigration Checkpoint as a means to anticipate threats, obstacles and disruptions to the territorial sovereignty of the Republic of Indonesia. Institutionally the Immigration Checkpoint is the work scope of the Directorate General of Immigration. In terms of the sea area there are international conventions that regulate the law of the sea which have an impact on immigration regulations that have a role in the Sea the Immigration Checkpoint namely the Cofference of Facilitation of Maritime Traffic, the convention on the ease of international maritime traffic held by the International Maritime Organization (IMO) in London. This Convention aims to harmonize government regulations with international regulations. The IMO FAL Convention was not fully adopted by Indonesia due to regulatory differences. The adoption of the IMO FAL Convention standard into regulations in Indonesia has a good influence on immigration as a standard for immigration checks for sea transport crews.